Leonard eaudiobook My fifty-year friendship with a remarkable man. - Shatner, William (Macmillan Audio, 2016)
"Shatner narrates his story with touching reverence for a dear friend...Shatner's authentic performance moves the story along with humor and sincerity, making the anecdotes all the more interesting and touching." — AudioFile Magazine A New York Times Bestseller Leonard Nimoy and William Shatner first crossed paths as actors on the set of The Man from U.N.C.L.E. Little did they know that their next roles as Spock and Captain Kirk, in a new science-fiction television series, would shape their lives in ways no one could have anticipated. In seventy-nine television episodes of Star Trek and six feature films, they grew to know each other more than most friends could ever imagine. Over the course of half a century, Shatner and Nimoy saw each other through personal and professional highs and lows. In this powerfully emotional audiobook, Shatner tells the story of a man who was his friend for five decades, recounting anecdotes and untold stories of their lives on and off set, as well as gathering stories from others who knew Nimoy well, to present a full picture of a rich life. As much a biography of Nimoy as a story of their friendship, Leonard is a uniquely heartfelt audiobook written and read by one legendary actor in celebration of another.